Canonical Relations of Sensomotoric Reactions to Light and Sound Stimulus - Dodig, Miroslav (Advances in Social Sciences Research Journal, 2014)
The sample subjects for this research list 20 subjects, of male gender, ranging from 20 to 22 years of age, a research of sensomotor reactions of multilateral and unilateral body parts was conducted. The process of collecting data and setting parameters was conducted using an instrument called the KINESIOMETER (M. Dodig, 1987), hooked up to an electronic computer, with an adequate periphery, with application of program support for analogue – digital conversion in the programming language SIMON'S BASIC. The basic reason for variability and covariability within the reaction time to light and sound signal incurred as the answer to efficient functioning of the perceptive system, channel permeability, efficiency of data decoding device and efficiency of data transmission and the efficient functioning of commissural connections between hemispheres represents the basic reason for obtained results. The obtained result incurred as the answer to a joint mechanism for structuring and speed of transmission impulse through afferent and efferent channels. In addition, the sensomotor reaction of multilateral parts to light and sound stimulus, due to its own preference of lateralization which manifest itself through curving of space towards the upper limbs, probably incurred as the answer to a larger direct autonomous and automatic use of the channels capacities and high-level organization of active effectors.